Physical collisions during elite rugby league match play and training: A stakeholder's perspective - Dixon, A. J.; Littlewood, M. A.; Cronin, C. J.; Twist, C.; Close, G. L. (International Journal of Sports Science & Coaching, 2025)
The purpose of this study was to explore rugby league stakeholders` perspectives of the tackle event, utilising qualitative approaches to gain further insight into this phenomenon. Nineteen stakeholders, comprising tactical coaches (n = 5), physiotherapists (n = 5), doctors (n = 5) and strength and conditioning coaches (n = 4) from every European 2023 Super League team (ESL), were recruited to participate in an online semi-structured interview, via the Microsoft Teams platform, facilitated by a moderator. Braun and Clarke's (2019) reflexive thematic analysis was performed to code and analyse the transcribed data; this established pattern-based interpretation and reporting from the dataset. The research findings can be divided into five crucial segments that illuminate our understanding of collision in rugby league: 1) simultaneous contact and the three-person tackle, 2) tackle height - calibration is critical, 3) the fundamental factors influencing tackle-related risks. 4) the graded exposure and philosophical approaches to contact training and games, 5) replacing toughness with resilience - the impact of game identity. The themes generated here provide comprehensive insights into stakeholders` perceptions of the optimal ways to perform collisions. This has implications for the identity of the game, and the subsequent law changes/ behavioural change models that aim to make the game safer, specific to rugby league. In line with previous research, the conclusions underline high-risk events in match play (blind-sided collisions and fatigue), providing a focus for areas of future research. Lastly, psychology in the tackle event is explored, highlighting the need for graded contact exposure from a physical and psychological perspective during tackle technique training.